The Multiple Violatings of Maxim in Indonesian Lawak Klub (ILK) by The Main Speakers in One Episode of Cara Cepat Menjadi Kaya (e-Journal of Linguistics, 2020)
The study deals with the types of maxim violation inIndonesian Lawak Klub (ILK) done by the mainspeakers. The objectives of study were to describe theviolation of maxim, to describe the dominant type ofmaxim violating and the reason of violating maxim. Thedata were the dialogue of main speakers in IndonesianLawak Club (ILK). This research was conducted usingdescriptive qualitative and focused on one episode ofcara cepat menjadi kaya. The findings showed thatthere are 70 violating of maxim of quantity, 71 violatingof maxim of quality, 144 vioalating of maxim ofrelevance, and 27 violating of maxim of manner. Thereasons of the dominant violating of maxim of relevanceare to widen discussion related to the topic and makeinteractive and atractive discussion.
Keywords: Multiple Violatings of Maxim; Indonesia Lawak Club (ILK); The Main Speaker